Компенсатор реактивної потужності з ВЧ-регулюванням величини коректуючої ємності - Будьонний, О.В.; Коваленко, Є.Ю.; Прокопець, М.А. (Технічна електродинаміка, 2012)
The problem of increasing the speed of the compensator reactive power and proposed technical solutions for improving compensation in the transition process on the basis of high-frequency control quantity correction capacity. Developed and theoretically justified method of reactive power compensation with variable in time loads. Established Matlabmodel of the compensator and considered its main modes of operation.